Analysis of the effectiveness of the OSHA steel erection standard in the construction industry. (November 2016) - Choe, Sooyoung; Yun, Sungmin; Leite, Fernanda
Highlights: Structural iron and steel workers have historically been high risk occupations. Regulatory intervention is one of the most influential factors. This study examined the impact of the revised steel erection standard. The revised standard was more effective on preventing less severe injuries than fatalities. Abstract: Regulatory intervention is one of the most influential factors in preventing occupational safety in the construction industry. In 2002, the United States (US) Occupational Safety and Health Administration (OSHA) revised the steel erection standard, which is designed to protect employees from steel erection related hazards. The purpose of this study was to examine a measurable impact of the revised OSHA 29 CFR 1926, Subpart R using data from the Bureau of Labor Statistics. This study identified four safety measures: fatality rate, days away injury rate, normalized fatality rate, and normalized days away injury rate. Descriptive and interrupted time series analyses were conducted to examine impacts of the revision of the standard on the safety of structural iron and steel workers. The findings indicate that fatality and days away injury rates of the structural iron and steel workers declined by 22.2% and 53.7%, respectively, after the implementation of the standard revision. In addition, two normalized safety indicators revealed that the reductions of fatality and days away injuries of the structural iron and steel workers were greater than those from the overall construction workers. This study provides evidence for the effectiveness of the revised standard in preventing overall occupational injuries in structural iron and steel workers in the US construction industry. In addition, the findings of this study demonstrate that the revised standard was more effective on preventing days away injuries than fatalities, which can guide future directions for policy makers and researchers.